BIOGRAFI DAN PEMIKIRAN FILSAFAT AL-FARABI: FILSAFAT EMANASI, KETUHANAN, KENABIAN, JIWA DAN AKAL - Firdaus, Firdaus; Saputra, Riki; Saifullah, Saifullah (Ensiklopedia of Journal, 2025)
This article discusses the biography and philosophical thoughts of Al-Farabi, a Muslim philosopher known as the "Second Teacher" after Aristotle. This study aims to reveal how Al-Farabi's life background influenced his thinking, especially in the philosophical concepts of emanation, divinity, prophecy, soul, and reason. Using a qualitative approach based on literature analysis, this study explores Al-Farabi's intellectual contribution in bridging classical Greek thought with Islamic traditions. The results show that Al-Farabi's thought makes a significant contribution in integrating rationality and spirituality, especially through the concept of emanation, which explains the hierarchical relationship between God and His creation. In addition, Al-Farabi's views on divinity, prophecy, and reason highlight the importance of reason in understanding reality and achieving happiness. This article also explores the relevance of Al-Farabi's thoughts in modern contexts, such as dialogue between religion and science, education, and the development of an ideal society. Al-Farabi's thinking remains a relevant intellectual heritage in responding to contemporary global and ethical challenges.Keywords: Al-Farabi, Islamic philosophy, emanation, divinity, reason, prophethood, contemporary relevance